Pro-Environmental Behavior Decisions in Face Mask Usage: A Pilot Study - Md Zaini, Syeliya; Joseph, Corina; Pudin, Susan; Amirrudin, Mira Susanti (Information Management and Business Review, 2023)
Human behavior and interaction with their surroundings vary from one another. Different people may engage and behave pro-environmental based on their beliefs and understanding of the consequences of environmental problems for themselves. The theory of planned behavior (TPB) and value belief norm theory (VBN) suggest that an individual perceives environmental pollution effects could influence their decision-making in daily activities. This study aimed to examine people’s behavior in using face masks and their perception of environmental consequences by integrating the TPB and VBN into a single conceptual framework. This study confirms that sub-factors, including biosphere, altruism, egoistic, awareness of consequences, and personal norms, are among the predictors that explain pro-environmental behavior in Malaysia. Additionally, the cultural factor significantly mediates the behavior. A questionnaire pilot survey was conducted among 50 visitors in a coastal area in Peninsular Malaysia. The Cronbach alpha test and descriptive analysis confirm the direct and mediatory effect of the causal of the variables in the TPB and VBN theory of pro-environmental behavior when making decisions in face mask usage. The research results validate the proposed TPB and VBN theory model linkages to clarify pro-environmental behavior.